Strategi Perencanaan SDM yang Efektif dalam Meningkatkan Kinerja Organisasi - Zulfikar, Zulfikar; Fatimah, Nur; Ikhsan, Ikhsan; Permadi, Rendhy Satriyo; Fadilla, Nur; Dinsar, Arfandy (Jurnal Ilmiah Manajemen & Kewirausahaan, 2023)
This journal discusses how to improve the performance of large companies through effective Human Resource (HR) plans. The research examined a wide range of companies and found that proactive career planning, skills-focused training, and adaptive performance appraisals can positively affect organizational performance. The results provide practical guidance for large company leaders to optimize HR strategies to improve efficiency and long-term performance